2001
DOI: 10.1046/j.1365-2524.2001.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Judging the ethics of qualitative research: considering the ‘ethics as process’ model

Abstract: Decision-making about the ethics of qualitative research is problematic where the research design is emergent, and the balance between risks and benefits for research subjects are difficult to ascertain prior to study implementation. The discourses of health/medical research ethics and those of social research are shown to be divergent and, furthermore, where ethics committees tie themselves to the health/medical model of ethical decision-making, qualitative research approaches can be disadvantaged. Having dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 43 publications
0
105
0
4
Order By: Relevance
“…Ethical issues in qualitative methodologies often emerge as research studies unfold, but current systems of ethical review are unable to address the nature of this process (Ramcharan and Cutliffe 2001). In practice, many qualitative researchers struggle to describe their research within the required format.…”
Section: 8mentioning
confidence: 99%
“…Ethical issues in qualitative methodologies often emerge as research studies unfold, but current systems of ethical review are unable to address the nature of this process (Ramcharan and Cutliffe 2001). In practice, many qualitative researchers struggle to describe their research within the required format.…”
Section: 8mentioning
confidence: 99%
“…It appears that RECs, by virtue of their foundation in biomedical research, use quantitative standards and methods leading to a paradigm bias against qualitative design, and concerned researchers have remarked on this over the last decade (Bledsoe, et al, 2007;Cutcliffe & Ramcharan, 2002;Haggerty, 2004;Librett & Perrone, 2010;Murphy & Dingwall, 2007;Ramcharan & Cutcliffe, 2001). In considering this matter, Parnis et al (2005) recognised the adherence of the health care institution REC to a dominant (biomedical) framework as a significant impediment to carrying out their research.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to bridge biomedical and social research ethics, Ramcharan and Cutcliffe (2001) have identified what they term an ethics as process model that focuses specifically on the intricate ethical dilemmas encountered in qualitative research, and which addresses areas of risk to participants that might not have been consid-ered by a REC. To this end, the authors recommend a monitoring process, whereby emerging ethical issues can be addressed as they occur, and the risk:benefit ratio of the research is balanced contemporaneously, initially inclining towards benefit rather than risk (Cutcliffe & Ramcharan, 2002;Ramcharan & Cutcliffe, 2001).…”
Section: Addressing Ethics In Ethnographymentioning
confidence: 99%
“…In a number of instances, qualitative research has been found to conflict with guidelines laid down by medical research ethics committees (Ramcharan & Cutcliffe 2001;Richards & Schwartz 2001). Research designs favoured by such committees often do not allow for the evolving nature of social-research questions and the range of people who may be involved in projects.…”
Section: Case Notes From Anthropologists In the Fieldmentioning
confidence: 99%